Universal causes of time overruns in construction projects: a systematic literature review - Pereira, Nathália Brandão; Kohlman Rabbani, Emilia Rahnemay; Silva, Maria Conceição da Costa (Technical and Scientific Journal Green Cities, 2024)
The satisfactory performance of a project is subject to a number of factors, including its execution on schedule. However, time overruns are frequent and have an impact on costs, the environment and society. This article aims to identify the main causes of delays in construction projects reported in the literature from different countries. The methodology adopted was a systematic literature review, extraction and statistical analysis of the causes indicated in articles over a 5-year period, in order to draw up a ranking of universal causes of delay in construction projects. A total of 68 studies were selected and 321 causes were obtained, from which the ranking of the 20 universal causes of delay was drawn up, the main ones being late payments to the contractor and frequent requests for changes/alterations to the project. From the study, it was possible to produce systematized knowledge about time overruns in projects to be applied in strategies to mitigate this problem. Identifying the causes of delays highlights issues to be prioritized, avoiding project stoppages and losses in essential investments for the economic and social development of countries.